Psychosocial Support After Galodo in Jorong Panti, Nagari Rambatan, Tanah Datar - Fitri, Ulya; Tusadiyah, Halimah; Arsy, Maulana Din; Wazeva, Zilpi; Dhi Putra, Dimas Angga (Mangabdi: Journal of Community Engagement in Religion, Social, and Humanities, 2024)
The Galodo disaster that struck Jorong Panti, Rambatan District, Tanah Datar, not only caused physical damage but also had a significant impact on the psychosocial condition of the community. The loss of homes, family members, and livelihoods created a need for assistance that goes beyond material support, emphasizing the importance of psychosocial care. This community service program aimed to restore the psychosocial condition of disaster victims, reduce post-disaster trauma, enhance community skills and knowledge, and support local economic recovery. The method used in this service was Participatory Action Research (PAR), allowing direct community involvement in the recovery process. Activities included psychological support for families and children, reviving Quranic learning programs (TPA) that had stopped, enhancing early childhood literacy through storytelling and drawing, and organizing political education to prepare for local elections, as well as entrepreneurship workshops to reignite the survivors' work spirit and improve their skills. The results of this program show that the psychosocial assistance provided successfully reduced trauma impacts, particularly on children, and increased community participation in social and religious activities. Additionally, the entrepreneurship and political education programs contributed positively to local economic recovery and improved the community’s political awareness. In the final week, the program concluded with religious competitions and cultural performances as a form of appreciation and an effort to strengthen social traditions and values. In conclusion, this community service program had a positive impact on the psychosocial and economic recovery of the Jorong Panti community following the Galodo disaster by actively involving the community in every phase of recovery